2021
DOI: 10.1002/adpr.202100036
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Polymer and Protein Microspheres with Inverse Photonic Glass Structure for Random Micro‐Biolasers

Abstract: The miniaturization of random lasers to the micrometer scale is challenging but fundamental for the integration of lasers with photonic integrated circuits and biological tissues. Herein, it is demonstrated that random lasers with a diameter from 30 to 160 μm can be achieved by using a simple emulsion process and selective chemical etching. These tiny random laser sources are made of either dye‐doped polyvinyl alcohol (PVA) or bovine serum albumin (BSA) and they are in the form of microporous spheres with mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…A possible interpretation for this effect is that the larger the laser size results in more lasing modes, thus, leading to a broader spectral width. Similar observations are also observed on random microlasers based protein microspheres with the inverse photonic glass structure [26].…”
Section: Size-dependent Lasing Characteristicssupporting
confidence: 81%
“…A possible interpretation for this effect is that the larger the laser size results in more lasing modes, thus, leading to a broader spectral width. Similar observations are also observed on random microlasers based protein microspheres with the inverse photonic glass structure [26].…”
Section: Size-dependent Lasing Characteristicssupporting
confidence: 81%
“…For instance, Ignesti et al [ 111 ] reported a maximum redshift of around 50 nm when increasing concentrations of intralipid in a dye solution. Other approaches, such as using larger microspheres diameters [ 116 ] and increasing the laser cavity lengths [ 117 ], also facilitate the peak wavelength redshift.…”
Section: Rl Emission Propertiesmentioning
confidence: 99%
“…SiO 2 -doped droplets instead do not show The observed behavior points out that the dielectric particles included in the droplets, besides gradually modifying the droplet's internal refractive index, may assemble into aggregates that act as sites suitable for the light confinement. 45,46 More specifically, such a system made up of a gain medium enclosing disordered ensembles of particles is defined as RL. 47 The aggregates behave as centers for the multiple scattering of light that above a certain pump threshold results in stimulated emission.…”
Section: ■ Results and Discussionmentioning
confidence: 99%